2010
DOI: 10.3892/ol_00000106
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among human papillomavirus infection, p16INK4a, p53 and NF-κB activation in penile cancer from northern Thailand

Abstract: Abstract. Human papillomavirus (HPV) E6 and E7 oncoproteins are essential factors for HPV oncogenesis. These E6 and E7 gene products play a central role in the induction of malignant transformation by interacting with several cellular regulatory proteins such as p16 INK4a , p53 and nuclear factor κB (NF-κB). In the present study, conducted in northern Thailand, HPV-DNA was detected in penile cancer cases using an in situ hybridization procedure and p16 INK4a , p53 and NF-κB were detected by immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…We have provided a detailed characterization of the genetic landscape of prostate cancer by DNA copy number aberrations found in HPV-positive and HPV-negative PSCCs, and demonstrated that these tumors display similar patterns of genetic aberrations despite the distinct pathogenetic mechanisms, with statistically significant changes in only a few small loci. It has been documented that HPV changes cell physiology inactivating RB and p53 pathways [ 28 , 29 ] and our genomic data shows copy number loss at 13q12.11-q34 (80% of HPV positive cases) and 17p13.3-p11.1 (63% of HPV positive cases), harboring RB1 and TP53 genes, respectively. However, these changes were not statistically significant in their difference from the HPV negative cohort.…”
Section: Discussionsupporting
confidence: 52%
“…We have provided a detailed characterization of the genetic landscape of prostate cancer by DNA copy number aberrations found in HPV-positive and HPV-negative PSCCs, and demonstrated that these tumors display similar patterns of genetic aberrations despite the distinct pathogenetic mechanisms, with statistically significant changes in only a few small loci. It has been documented that HPV changes cell physiology inactivating RB and p53 pathways [ 28 , 29 ] and our genomic data shows copy number loss at 13q12.11-q34 (80% of HPV positive cases) and 17p13.3-p11.1 (63% of HPV positive cases), harboring RB1 and TP53 genes, respectively. However, these changes were not statistically significant in their difference from the HPV negative cohort.…”
Section: Discussionsupporting
confidence: 52%
“…We demonstrated the correlation between HPV infection and nuclear and/or cytoplasmic NF-κB expression using the Fisher's exact probability test. HPV infection was considered to activate NF-κB resulting in cell transformation (11,12,24).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the HPV-independent carcinogenesis is not fully understood. Although disruption of the p53 pathway in HPV-negative penile SCC has been described [9], others did not find any difference in p53 expression between HPVpositive and HPV-negative penile SCC [10].…”
Section: Introductionmentioning
confidence: 97%